CO2 laser and/or fluoride enamel treatment against in situ/ex vivo erosive challenge - Maísa Camillo JORDÃO; Gustavo Manzano FORTI; Ricardo Scarparo NAVARRO; Patrícia Moreira FREITAS; Heitor Marques HONÓRIO; Daniela RIOS
ABSTRACT Objective This in situ/ex vivo study investigated the effect of CO2 laser irradiation and acidulated phosphate fluoride gel (APF) application, separately and in combination, on enamel resistance to erosion. Material and Methods During 2 experimental 5-day crossover phases, 8 volunteers wore intraoral appliances containing bovine enamel blocks which were submitted to four groups: 1st phase - control, untreated and CO2 laser irradiation, 2nd phase - fluoride application and fluoride application before CO2 laser irradiation. Laser irradiation was performed at 10.6 µm wavelength, 5 µs pulse duration and 50 Hz frequency, with average power input and output of 2.3 W and 2.0 W, respectively (28.6 J/cm2). APF gel (1.23%F, pH 3.5) was applied on enamel surface with a microbrush and left on for 4 minutes. Then, the enamel blocks were fixed at the intraoral appliance level. The erosion was performed extraorally 4 times daily for 5 min in 150 mL of cola drink. Enamel loss was measured profilometrically after treatment and after the in situ phase. The data were tested using one-way Repeated Measures Anova and Tukey's test (p<0.05). Results CO2 laser alone (2.00±0.39 µm) did not show any significantly preventive effect against enamel erosion when compared with the control group (2.41±1.20 µm). Fluoride treated enamel, associated (1.50±0.30 µm) or not (1.47±0.63 µm) with laser irradiation, significantly differed from the control. Conclusion The APF application decreased enamel wear; however, CO2 laser irradiation did not enhance fluoride ability to reduce enamel wear.